Accelerating Varietal Turnover Through Digital Multi-Stakeholder Platforms (MSPs) in Tanzania - Rickards, Chima; Rutsaert, Pieter; Ochieng, Justus; Ojiewo, Christopher Ochieng; Rubyogo, Jean Claude; Radegunda, Kessy; Mwakatwila, Atupokile; Kadege, Edith; Kalamera, Sylvia; Madeni, Joachim; Birachi, Eliud; Lesedy, Victor; et al. (2025)
Varietal turnover (VTO) - the timely replacement of old seed varieties with newer, improved ones - remains a challenge for Tanzania’s agricultural productivity, especially for openpollinated crops such as common beans, groundnuts, and sorghum. Despite clear benefits of improved varieties, including yield gains of more than 50%, better disease resistance, and higher income potential, adoption rates remain low. Tanzania’s predominantly informal seed system, where over 97% of planting material is sourced from farmer-saved seeds or grain markets, contributes to this slow uptake, with the average age of bean varieties on the market reaching 20 years in 2020. The Accelerated Varietal Turnover of Open-Pollinated Crops (ACCELERATE) project, led by the Alliance of Bioversity International and CIAT/PABRA in collaboration with CIMMYT, TARI, and TOSCI, and funded by the Gates Foundation, aims to tackle these systemic barriers.